Analisa Migrasi Sistem Dari Microsoft Dynamics Axapta - Reiner Tunarso; Alexander Setiawan; Leo Willyanto Santoso (Jurnal Infra, 2017)
PT. X is a distributor of motorcycle that also sells motorcycle parts located in Surabaya. The sales process conducted by PT. X until present is the user come to seller, then makess an order. PT. X doesn’t have a website to sell online so PT. X only has customers around the Surabaya.PT. X has a website that contains about the profile companies and motor cycle products along specification. PT. X using applications ERP (Enterprise Resource Planning) system based on Microsoft is Microsoft Dynamics Axapta. PT. X initially used with Oracle-based ERP application and in 2014 switched to Microsoft Dynamics Axapta. These application selected by PT. X as in the company using the Microsoft platform that easily integrated with other Microsoft Office and modules contained in Microsoft Dynamics Axapta easy for custom so that it can adapt to needs of company and business processes PT. X.